(untitled) (Minerva, 2020)
In 1609, Quevedo translated Pseudo-Phocylides’ Sentences, which he also quoted in Anacreón castellano (Castilian Anacreon), through two fragments with a slightly modified translation. The collation of these different translations into Spanish of the work attributed to the Greek poet reveals possible stylistic reasons and a purpose of adaptation to the context in which they are included. Likewise, this analysis confirms Quevedo’s tendency to rewrite and to freely quote classic texts in Spanish.